Fabrication of Cellulose Nanocrystal (CNCs) Based Biosorbent From Oil Palm Trunks Through Acid Hydrolysis With Sonication Assisted and Adsorption Kinetic Study - Pra Cipta Buana Wahyu Mustika; Mega Mustikaningrum (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2022)
Developing cellulose nanocrystal (CNCs) preparation techniques is a challenge confronted by many researchers. The advantages of property remain the reason for research to be developed. To deal with this issue, it is essential to conduct research related to process optimization, particularly in the hydrolysis process, which is the primary step in forming CNCs. In this study, the effect of sonication-assisted hydrolysis time was investigated. XRD characterization showed that the CNCs formed where the first group with specific peaks indicated. The crystallinity of CNCs decreased with increasing sonication duration, indicating that sonication-assisted hydrolysis was nonselective. The crystallinity of CNCs obtained for 15, 30, and 45 min was 61.6, 55.0, and 48.4 %, respectively. For sonication duration variations of 15, 30, and 45 min, the hydration diameter of CNCs was nearly identical at 42.35 ± 27.10, 42.99 ± 29.46, and 42.63 ± 29.49 nm, respectively. Similarly, the removal of methylene blue can be achieved using CNCs bio-adsorbent. The results of percent removal of methylene blue under sonication treatment of 15, 30, and 45 min of sonication were 73.34; 73.62; 72.86 %, respectively. The adsorption rate of CNCs follows the pseudo-second-order kinetic model, with the adsorption values under sonication treatment of 15, 30, and 45 min were 0.075 ± 0.008; 0.166 ± 0.013; 0.078 ± 0.005 g mg-1 min-1, respectively.